THE POWER OF MAJOR SPORTING EVENTS: TRANSFORMING DESTINATION IMAGE THROUGH PROMOTION AND EXPERIENCE - Girsang, Zefanya Andryan; Mulyono, Lalu Edy Herman; Rinuastuti, Baiq Handayani; Roodhi, Mohammad Najib (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024DO - 10.24843/EEB.2024.v13.i11.p17, 2024)
The Mandalika MotoGP World Championship 2023 holds a pivotal role in Mandalika’s destination branding process. This study seeks to discern and evaluate the impact of the event on Mandalika’s destination image, positioning it among the world’s premier tourist destinations. Central to this investigation is the meticulous development of the 6A’s of destination (comprising Attractions, Amenities, Accessibility, Activities, Accommodations, and Ancillary services) and the strategic promotional mix. Notably, the spectators’ event experience emerges as a crucial mediator, shaping Mandalika’s image.  The author sent a questionnaire to motorsports event attendees to address study objectives. The questionnaire was sent directly to those who attended the Mandalika MotoGP 2023 event. The email address was obtained from many travel companies that assisted tourists attending the Mandalika MotoGP 2023. The survey includes questions regarding participants' background information such as age, gender, and occupation. The findings underscore the substantial influence of synergizing the 6A’s of destination with an effective promotional mix, ultimately enhancing Mandalika’s allure for travelers.